7-(diethylamino)-4-methyl-3-vinylcoumarin as a new important intermediate to the synthesis of photosensitizers for DSSCs and fluorescent labels for biomolecules - Martins, S (2021)
munity in last decades due to their very significant pharmacological activity and due to their excellent photophysical and spectroscopic properties. The design and synthesis of new efficient organic photosensitizers for DSSC’s, considered promising photovoltaic devices, is of utmost importance to be used in electric energy production from solar irradiation. On the other hand, compounds with a similar synthetic strategy are essential to develop new fluorescent labels used on very sensitive analytical techniques to detect and track biomolecules in very important areas, such as cellular biology, medicine, medicinal chemistry and environmental science. In this work, using 7-(diethylamino)-4-methyl-3-vinylcoumarin as an intermediate, we developed a simple, low cost and efficient synthetic strategy to produce new promising photosensitizers for DSSCs and fluorescent labels for biomolecules.